Adapting Caring Contacts for Veterans in a Department of Veterans Affairs Emergency Department: Results From a Type 2 Hybrid Effectiveness-Implementation Pilot Study - Landes, Sara J.; Jegley, Susan M.; Kirchner, JoAnn E.; Areno, John P.; Pitcock, Jeffery A.; Abraham, Traci H.; McBain, Sacha A.; Singh, R. Sonia; Bollinger, Mary J.; Painter, Jacob; Woods, Jack A.; Curtis, Nyssa D.; et al. (Frontiers in Psychiatry, 2021)
Transitions in care, such as discharge from an emergency department (ED), are periods of increased risk for suicide and effective interventions that target these periods are needed. Caring Contacts is an evidence-based suicide prevention intervention that targets transitions, yet it has not been widely implemented. This pilot study adapted Caring Contacts for a Department of Veterans Affairs (VA) ED setting and population, created an implementation toolkit, and piloted implementation and evaluation of effectiveness. To inform adaptation, qualitative interviews were conducted with stakeholders. Data were used by an advisory board comprised of stakeholders, experts, and veterans to make adaptations and develop an implementation planning guide to delineate steps needed to implement. Key decisions about how to adapt Caring Contacts included recipients, author, content, and the schedule for sending. Pilot implementation occurred at one VA ED. Caring Contacts involved sending patients at risk of suicide brief, non-demanding expressions of care. Program evaluation of the pilot used a type 2 hybrid effectiveness-implementation design to both pilot an implementation strategy and evaluate effectiveness of Caring Contacts. Evaluation included qualitative interviews with veteran patients during implementation. VA electronic health records were used to evaluate VA service utilization in the six-month periods immediately before and after veterans were delivered their first Caring Contact. 475 veterans were mailed Caring Contacts and the facility continued adoption after the pilot. Participants were positive about the intervention and reported feeling cared about and connected to VA as a result of receiving Caring Contacts. This project developed an implementation planning process that successfully implemented Caring Contacts at one site. This can be used to further implement Caring Contacts at additional VA or community EDs.